Growing Numeral Literacy Skills through Science, Technology, Engineering, Arts, Mathematics Based on Local Wisdom - Aini, Kurratul; Misbahudholam AR, Muhammad; Ridwan, M. (MIMBAR PGSD Undiksha, 2024)
Literacy and numeracy competencies are fundamental competencies in the industrial era 5.0. Numeracy skills are also needed in trade, health, education, etc. Literacy skills are required to face global challenges, solve problems, make appropriate decisions, and understand natural and social phenomena. Literacy and numeracy skills are essential abilities and are the basis of education. This study aims to analyze the implementation of STEAM learning based on local wisdom and how it affects numeracy and literacy skills in elementary school level. This mixed-methods research uses a Sequential Exploratory model/design and data collection using observation, interviews, and tests. The results showed that teachers in implemented STEAM learning based on local wisdom according to the indicators: observation, new ideas, innovation, creativity, and society. In the process, the teacher integrates local wisdom values into learning in the last step, namely culture. The pre-test results showed 40% of students' completeness with an average score, while the post-test showed 80% of students' totality with an average score, increasing student learning outcomes in class IV elementary school. The results of the paired samples t-test also show a significance value, which means that STEAM learning based on local wisdom affects students' numeracy and literacy skills in fourth grade. It is hoped that literacy and numeracy will become supporting materials for strengthening the literacy movement the school has carried out. This article's literacy and numeracy applications will continue to develop and vary according to the diverse context of needs and socio-cultural conditions of schools.